Splitting Orders - Bernhardt, Dan; Hughson, Eric (Review of Financial Studies, 1997)
A standard presumption of market microstructure models is that competition between risk-neutral market makers inevitably leads to price schedules that leave market makers zero expected profits conditional on the order flow. This article documents an important lack of robustness of this zero-profit result. In particular, we show that if traders can split orders between market makers, then market makers set less-competitive price schedules that earn them strictly positive profits and hence raise trading costs. Thus, this article can explain why somebody might willingly make a market for a stock when there are fixed costs to doing so. The analysis extends to a limit order book, which by its nature is split against incoming market orders: equilibrium limit order schedules necessarily yield those agents positive expected profits.